SMART ANTENA - Winata, Tony (Jurnal Teknik Elektro, 2003)
A combination of an antenna array and an adaptive processor can perform a radiationpattern in the direction of arriving signal and at the same time reject any interfering signalor noise from other directions. With the variable weights on every element, signal processorcan easily adjust the weight by a simple adaptive technique based on the least-mean-squares(LMS) algorithm. During the adaptive process an incoming signal simulates a receivedsignal from a desired look direction, this allow the array system to learn so its directivitypattern has a main lobe in the previously specified look direction. At the same time, thearray processing system reject any interfering noise and signals, whose directions ofpropagation are different from the desired look direction, by forming nulls in the antennapattern. The technique described are simulated by Matlab. Substantial reductions in noiseand any other signals are demonstrated. The results are the arrays can be used over a widerange of frequencies and the more elements of the array the used more acurate the pattern.Keywords: simulation, random real number, forecasting, mean squares, scenario